Access to medical care and its association with physical injury in adolescents: a cross-national analysis. Issue 1 (27th September 2022) - Pagnotta, Valerie F.; King, Nathan; Donnelly, Peter D.; Thompson, Wendy; Walsh, Sophie D.; Molcho, Michal; Ng, Kwok; Malinowska-Cieślik, Marta; Pickett, William
Abstract : Background: Strong variations in injury rates have been documented cross-nationally. Historically, these have been attributed to contextual determinants, both social and physical. We explored an alternative, yet understudied, explanation for variations in adolescent injury reporting—that varying access to medical care is, in part, responsible for cross-national differences. Methods: Age-specific and gender-specific rates of medically treated injury (any, serious, by type) were estimated by country using the 2013/2014 Health Behaviour in School-aged Children study (n=209 223). Available indicators of access to medical care included: (1) the Healthcare Access and Quality Index (HAQ; 39 countries); (2) the Universal Health Service Coverage Index (UHC; 37 countries) and (3) hospitals per 100 000 (30 countries) then physicians per 100 000 (36 countries). Ecological analyses were used to relate injury rates and indicators of access to medical care, and the proportion of between-country variation in reported injuries attributable to each indicator. Results: Adolescent injury risks were substantial and varied by country and sociodemographically. There was little correlation observed between national level injury rates and the HAQ and UHC indices, but modest associations between serious injury and physicians and hospitals per 100 000. Individual indicators explained up to 9.1% of the total intercountry variation in medically treated injuries and 24.6% of the variation in serious injuries. Conclusions: Cross-national variations in reported adolescent serious injury may, in part, be attributable to national differences in access to healthcare services. Interpretation of cross-national patterns of injury and their potential aetiology should therefore consider access to medical care as a plausible explanation.